SHASHI DESHPANDE’S INDIAN FEMININE PROTAGONISTS - Elamadurthi, Ranjit Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Shashi Deshpande’s novels usually deal with female protagonists striving to search or find their own selves. Deshpande’s heroines do it through writing andultimately take a resolution in their lives. The unexpressed and often ignored issues of women from theirunknown regions are clearly portrayed in her novels.